‘Biodiversity’ in Extinction Rebellion’s words: an ecostylistic examination of a beneficial text - Daniela Francesca Virdis (Cogent Arts & Humanities)
This article refers to the ecological rhetorical terms ‘marker word’ and ‘environet’ and to the ecolinguistic terms ‘beneficial discourse’ and ‘ecosophy’, and applies the stylistic theories of foregrounding, point of view, and metaphor to explore two diverse but complementary sets of linguistic data pertaining to the environet and containing the marker word ‘biodiversity’. The first set of data is realised by four definitions of the noun ‘biodiversity’ provided by the Oxford English Dictionary and by three recent ecology and environment dictionaries and textbooks. Taking these definitions as a starting point, the second set of data consists of a text drawn from the environmental website of the international movement Extinction Rebellion incorporating the same marker word and showing its use in the beneficial context of an ecologically committed text in line with the ecosophy of this article and its seven norms. The article has a two fold research purpose: 1. To identify the beneficial ecostylistic strategies utilised in the dictionary and textbook definitions and in the text from XR’s website; 2. To promote these beneficial ecostylistic strategies and the beneficial messages they convey among the general public.